Implementasi Fitur Electronic Customer Relationship Management pada Rekam Medis - Nuri Cahyono (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
Managing relationships with customers is a strategy that is currently required by each agency as a strategic part of the business in order to increase customer loyalty, in this case including both the health care institutions hospitals, health centers and other health care institutions. This study aims to implementation the features of Electronic Customer Relationship Management for the patient medical record. With this implementation of health care institutions will be able to apply the technology to help so that patients gain the ease and convenience of services provided which will later be formed customer loyalty.